A Comparative Study to Check Awareness of Food Labeling between Nutrition and Non-Nutrition Undergraduate Students (Indian Journal of Public Health Research & Development, 2021)
Background: Food labeling can be a very important public health tool in providing consumers withinformation which may help them to make informed decisions towards choosing good nutrition and health.Objective: The main objectives were to assess the awareness and importance of food labeling amongstudents of nutrition and non-nutrition groups and to study the type of information students generally lookon the food label while buying a product. Methods: A cross-sectional study was conducted at St. FrancisCollege for Women in which 240 undergraduate college girls aged between 18-21 years of age were selected.The questionnaire was used to assess knowledge of the participants towards food labeling. Results: Theresults showed that 89.16% of nutrition and 57.5% of non-nutrition students were aware of FSSAI,78.33%of nutrition and 60.83 % of non-nutrition students were aware of ISI, 80.8% of nutrition and only 12.5%of non-nutrition students were aware of FPO,100% of nutrition and 32.5% of non-nutrition students wereaware of trans fat,98.3% of nutrition and 86.66% of non-nutrition students reported that food additives andpreservatives affect the state of health, 85.8% of nutrition and 38.33% of non-nutrition students reported thatMSG has harmful impact on human health,91.66% of nutrition and 92.5% of non-nutrition students wereaware of QR codes. Conclusion: The study concluded that those pursuing a degree in nutrition appear to bemore capable of interpreting food label information and incorporating that information into a healthy dietthan non-nutrition students. Hence, nutrition education can be a powerful tool to create awareness on foodlabel usage.
Keywords: Food label, Consumer awareness, Knowledge, Nutrition information.